Consequences of Strands of Democratic Socialism in India: Exploring the Reflections of Socialism in the Indian Constitution (Journal of Advances and Scholarly Researches in Allied Education, 2011)
We also addressed the reflection of Liberalism in the Constitution of India. In this section, we are going to study the reflection of Socialism in the Constitution. It is mainly to review Dr. B. R. Ambedkar's State Socialism and Pandit Jawaharlal Nehru's Democratic Socialism, and its expression in the Indian Constitution. The word socialist was initially not in the preamble. It was annexed to the Preamble by the 42nd Constitution Amendment in 1976. The definition of Socialism was then made explicit. And India's commitment to this ideal has been underlined and echoed.' Nehru omitted the term' socialism from the Objective Resolution.' The word Socialist has not been stated in the Constitution. The Constitutional Assembly could not obtain a general majority, a concise principle of socialism. To conclude that 'socialism' is everyday politics for social regeneration, and that democratic constitutions are inseparably linked to the struggle for economic growth, Fabian and Laski-ite were required. The Constituent Assembly noticed that the Constitution must be dedicated to some form of socialism and the social reconstruction of India in the Priorities Resolution and the discussion on it. 2 The Mixed Economy in India was initially adopted. A mixed economy policy is funded by the government in which the public and private sectors coexist side by side. However, so far, commercial companies have been rigorously governed by the government. In reality, however, government policies are heading towards disinvestment and rising privatisation. And the measures tend to be that there is a rising wealth inequality. Economic inequality, it is obvious, is not the intent and spirit of India's Constitution. So, the segment 'Socialism in the Indian Constitution Reflection of Dr. B.R. Ambedkar and Reflection of Pandit Jawaharlal Nehru' fulfills the need of the scholar to understand the nature of socialism reflected in the Constitution.